The Effect of a Period of Basic Football Skills Training on Perceived Competence and Physical Abilities of Beginner Football Learners in Iraq: The Moderating Role of Age - Alsarki, Mokdad Bashir Hussein; Serjuei, Zahra; Alsarkhi, Mohammed Hussein Hameedi; Zahedi , Hamid (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The purpose of the present study was to examine the effect of a period of basic football skills training on perceived competence and physical abilities among boys aged 9 to 12 years.Methods and Materials: The research method was quasi-experimental with a pretest–posttest design and a control group. The statistical population consisted of elementary school boys and football school trainees in Maysan City, Iraq. From this population, 60 participants were purposefully selected and assigned to four groups: three experimental groups aged 9–10, 10–11, and 11–12 years (each consisting of 15 participants) who participated in the training protocol, and one control group (15 participants) who received no intervention. The mean age of the control group was 10.6 years, which was approximately in the middle of the experimental age range. The training protocol lasted eight weeks with three sessions per week and focused on basic football skills, including dribbling, passing, shooting, coordination, and small-sided games. The research instruments included the Perceived Physical Competence Scale for Children and a set of standardized physical fitness tests such as the Yo-Yo test, Sargent jump test, Illinois agility test, 20-meter sprint, and sit-and-reach test. Data were analyzed using analysis of covariance (ANCOVA) and Bonferroni post hoc tests.Findings: The results showed that basic football skills training had a significant effect on perceived competence (F = 15.61, p < .001, η² = .31) and physical abilities (F = 18.92, p < .001, η² = .35). Moreover, the interaction effects indicated a moderating role of age, as children aged 11 to 12 demonstrated the greatest improvement compared to younger groups, while the control group exhibited minimal changes from the pretest.Conclusion: These results underscore the importance of designing and implementing structured sports programs in schools and extracurricular contexts and can serve as an effective model for the holistic development of children during the critical ages of 9 to 12 years.